Accounting 4.0: a study of multiple cases in sergipan accounting organizations - Dos Passos Santos, Eliana; Silva, Debora Eleonora Pereira da (Advances in Scientific and Applied Accounting, 2023)
Objective: The research seeks to understand how accounting organizations in the State of Sergipe are using the technological elements of industry 4.0. Method: Qualitative in nature, exploratory and descriptive, the strategy of studying multiple cases in three accounting organizations was used. The sources of evidence were semi-structured interviews and document analysis. Bardin’s (1977) content analysis was used. Results: The way of using IoT, IoS, automation, M2M, big data analytics, cloud computing, systems integration, cybersecurity, QR code and virtual reality, identified technological elements of Industry 4.0, showed disagreement in their classification in relation to the literature of Industry 4.0. The principles are the same as those of Industry 4.0: interoperability; virtualization; decentralization; real-time capacity; service orientation and modularity. The results sought are: vertical, horizontal and end-to-end integration. However, the latter was not identified in any of the cases studied, even though it is the main desired result. The main challenges faced by the surveyed companies were: security and digital protection, students’ technical capacity, and resistance to changes presented by their customers. Contributions: This research contributes to the transition to a 5.0 society; advancing in academic studies; for Sergipe’s Regional Accounting Council (CRC/SE), it provides strategies to improve the training of accounting professionals; for software companies, it presents organizations’ quest for greater efficiency in production; for accounting organizations, it helps in the implementation of an Accounting 4.0 by presenting the challenges to be faced.